Correlation between Cytomegalovirus (CMV) Infection in Children with Cerebral Palsy (CP) and Future Anxiety among Parents - Anindya, Isti; Lestari, Nur Eni (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2021)
ABSTRACTIntroduction: One of the causes of Cerebral Palsy (CP) is a viral infection in the mother during pregnancy. The most recorded infections were Cytomegalovirus (CMV) infections. Inappropriate parenting can affect the psychological condition of CP children. Psychological conditions that are not good can cause the child's immune system to decrease and increase the risk of CMV reactivation. This is one factor in the emergence of parental anxiety about the future sustainability of their CP children. Objectives: It was to determine the relationship of anti-cytomegalovirus (CMV) Immunoglobulin G in children with CP with future anxiety among parents. Methods: The design of this study used a cross-sectional approach that using CP children and their parents. Serological examination used the ELFA (Enzyme-Linked Fluorescent Assay) method for 40 CP children and a questionnaire on the future anxiety of parents of children with special needs were answered directly by the parents of CP children, 40 fathers and 40 mothers. Analysis of the research data used Spearman Rank. Results: The results of this study found an anti-CMV IgG seropositive relationship in CP children with future anxiety in fathers (p-value = 0.022; a 0.05) and mothers (p-value = 0.011; a 0.05). Discussion: If anxiety in parents has not good treatment, it will impact the care of CP children, the developmental progress of CP children will not optimal.Â ABSTRAKPendahuluan: Salah satu faktor penyebab Cerebral Palsy (CP) adalah infeksi virus yang terjadi pada ibu selama kehamilan. Infeksi yang tercatat paling banyak adalah infeksi Cytomegalovirus (CMV). Pengasuhan yang tidak sesuai dapat mempengaruhi kondisi psikis anak CP. Kondisi psikis yang tidak baik dapat menyebabkan sistem imun anak turun dan meningkatkan risiko reaktivasi CMV. Hal ini menjadi salah satu faktor munculnya kecemasan orangtua terhadap keberlangsungan masa depan anak CP mereka. Tujuan: Menganalisis hubungan seropositif IgG anti-CMV pada anak CP dengan kecemasan masa depan orangtua. Metode: Design penelitian ini menggunakan pendekatan cross sectional yang dilakukan pada anak CP dan orang tua. Pemeriksaan serologi menggunakan metode ELFA (Enzyme Linked Fluorescent Assay) yang dilakukan pada 40 anak CP dan lembar kuesioner kecemasan masa depan orang tua anak berkebutuhan khusus yang dijawab langsung oleh orangtua anak CP yang terdiri dari 40 ayah dan 40 ibu. Analisis data penelitian ini menggunakan Spearman Rank. Hasil: Hasil penelitian ini menemukan hubungan seropositif IgG anti-CMV pada anak CP dengan kecemasan masa depan pada ayah (nilai p=0,022; a0,05) dan ibu (nilai p=0,011; a0,05). Diskusi: Kecemasan yang tidak dapat ditangani dengan baik akan berdampak pada pengasuhan anak CP sehingga kemajuan perkembangan anak CP tidak optimal.